2007
DOI: 10.1074/jbc.m610906200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nanog Expression by Phosphoinositide 3-Kinase-dependent Signaling in Murine Embryonic Stem Cells

Abstract: Embryonic stem (ES) cell pluripotency is regulated by a combination of extrinsic and intrinsic factors. Previously we have demonstrated that phosphoinositide 3-kinase (PI3K)-dependent signaling is required for efficient self-renewal of murine ES cells. In the study presented here, we have investigated the downstream molecular mechanisms that contribute to the ability of PI3Ks to regulate pluripotency. We show that inhibition of PI3K activity with either pharmacological or genetic tools results in decreased exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
143
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(160 citation statements)
references
References 54 publications
16
143
0
1
Order By: Relevance
“…20 Inhibition of PI3K/Akt signaling with LY-294002 reduces mouse ES proliferation, pluripotency, and Nanog expression. 18,19,21,22 Those effects are similar to the effects of overexpressing DLK in mouse ES cells ( Fig. 3C and D).…”
Section: Dlk Kinase Activity Is Upregulated Upon Differentiation Of Msupporting
confidence: 73%
See 4 more Smart Citations
“…20 Inhibition of PI3K/Akt signaling with LY-294002 reduces mouse ES proliferation, pluripotency, and Nanog expression. 18,19,21,22 Those effects are similar to the effects of overexpressing DLK in mouse ES cells ( Fig. 3C and D).…”
Section: Dlk Kinase Activity Is Upregulated Upon Differentiation Of Msupporting
confidence: 73%
“…[18][19][20][21][22] Many proteins and signaling pathways involved in proliferation or pluripotency are modulated by PI3K/Akt including Gsk3b/Myc, FoxO, mTOR and Tbx3/Nanog pathways. 8,21,22,41-43, In this study, for the first time, DLK was demonstrated to be an Akt substrate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations